Sexual Dimorphism and Aging as Determinants of Serum Lipid Profiles and Cardiovascular Risk - Majchrzak, Mateusz; Graczyk, Natalia; Graczyk, Martyna; Wisoky, Wiktor; Czapla, Natalia; Ziółkowska, Weronika; Stróżyńska, Ewelina; Łopińska, Joanna; Majchrzycka, Marta; Ignyś, Piotr (Journal of Education, Health and Sport, 2026)
The complex variability of circulating blood lipid profiles serves as a fundamental physiological indicator for the onset and progression of numerous metabolic and chronic conditions. It is clinically well-established that dyslipidemia—a multifaceted metabolic state characterized by pathologically elevated lipid concentrations—functions as a primary driver in the pathogenesis of atherosclerosis and subsequent cardiovascular disease. Given that the systematic reduction of these lipid fractions, whether through pharmacological intervention or lifestyle modification, can drastically improve a patient’s long-term cardiovascular prognosis, a nuanced understanding of lipid distribution is critical for effective clinical management. This review provides a comprehensive analysis of the various biological determinants that govern these fluctuations, with a particular emphasis on the distinct roles of sex-based hormonal profiles and age-related physiological shifts. By examining the interplay between these factors, we aim to elucidate how they independently and synergistically influence the serum concentrations of triglycerides, low-density lipoprotein (LDL) cholesterol, and high-density lipoprotein (HDL) cholesterol. Furthermore, the discussion explores how these demographic variables modulate the metabolic pathways responsible for both the accumulation of pro-atherogenic particles and the efficiency of reverse cholesterol transport, ultimately shaping an individual’s overall cardiovascular risk profile.